Improved Permafrost Protection Using Air Convection and Ventilated Shoulder Cooling Systems - Goering, Douglas J.; University of Alaska Fairbanks. Institute of Northern Engineering
This report focuses on the effectiveness of air convection embankments (ACE) and ventilated shoulder (VS) cooling systems designed to cool foundation soils and preserve permafrost beneath roadway embankments. The four main sections of the report include a literature review, an analysis of field data from the Thompson Drive Experimental Feature near Fairbanks, an analysis of data from the Alaska Highway Dot Lake Experimental Feature site, and a discussion of techniques for modeling ACE and VS structures using the GeoSlope Temp/W modeling package. Fifteen years (2005-2020) of data from the Thompson Drive site are analyzed using contour plots of average annual temperatures within the embankment and underlying foundation soils along with time series of temperature behavior at specific locations throughout the embankment test sections. Similarly, data from the Alaska Highway site is analyzed over a three-year period (June 2017 to May 2020) by examining average annual temperatures at an array of measurement points within the embankment test sections and underlying soils. In all cases the data indicates a strong overall cooling influence, particularly in the layers underlying the VS structures.